1990
DOI: 10.1007/bf03220941
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum alloy 6013 sheet for new U.S. Navy aircraft

Abstract: The recently developed aluminum alloy 6013-T6 has been selected for the fuselage skin and other applications on the u.s. Navy's P-7 A airplane, in place of the traditional 2024-T3 clad sheet. Alloy 6013-T6 is naturally corrosion resistant, like the well-established alloy 6061, and hence is used unclad. Its fatigue strength, fatigue crack growth and fracture toughness compare favorably with 2024-T3. Replacement of alloy 2024 with alloy 6013 also reduces manufacturing costs for formed parts, because 6013 is rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The 6013 aluminum alloy, a Cu-added Al-Mg-Si-Cu alloy of the 6XXX series, was first produced in the 1970s for the automotive sector with the aim of improving fuel efficiency. In later years, as a result of tests carried out at Lockheed and Alcoa Laboratories, the 6013 aluminum alloy was found to provide higher corrosion resistance despite having almost similar mechanical properties to the 2024 aluminum alloy used in aircraft, and it has begun to be used by Lockheed as structural aircraft material [8]. During aging in the Al-Mg-Si-Cu aluminum alloy, the needle-like β" phase transforms into the rodlike β'+ lathlike Q'-Al5Cu2Mg8Si6 phases.…”
Section: Introductionmentioning
confidence: 99%
“…The 6013 aluminum alloy, a Cu-added Al-Mg-Si-Cu alloy of the 6XXX series, was first produced in the 1970s for the automotive sector with the aim of improving fuel efficiency. In later years, as a result of tests carried out at Lockheed and Alcoa Laboratories, the 6013 aluminum alloy was found to provide higher corrosion resistance despite having almost similar mechanical properties to the 2024 aluminum alloy used in aircraft, and it has begun to be used by Lockheed as structural aircraft material [8]. During aging in the Al-Mg-Si-Cu aluminum alloy, the needle-like β" phase transforms into the rodlike β'+ lathlike Q'-Al5Cu2Mg8Si6 phases.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with 2024-T3 aluminum alloy, the strength of 6013-T6 increases by 12%, but the corrosion resistance is similar, and it has higher anti-fatigue performance and damage-tolerance. 6013-T6 aluminum alloy can replace 2024-T3, T4 on the application of Navy's P-7A aircraft, airbus A380 and so on [9,10]. The latest study found that the performance of 6013 aluminum alloy can be further improved by optimizing the alloy composition, large strain processing and subsequent heat treatments [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium alloys are very important structural materials. Particularly high requirements are imposed on materials for aircraft constructions where high strength Al-Cu-Mg, Al-Zn-Mg-Cu, Al-Li and recently Al-Mg-Si alloys are used [1,2]. The increased interest of automotive industry in aluminium alloy applications (Al-Mg, Al-Mg-Si) has resulted in an important development of new alloys and a considerable efforts for property optimisation of existing alloys during the last decade [3,4].…”
Section: Introductionmentioning
confidence: 99%